1981
DOI: 10.2134/jeq1981.00472425001000010020x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Volatilization from Liquid Swine Manure Applied to Cropland

Abstract: Randomized complete block design field experiments were conducted to determine the effects of rates and methods of liquid swine manure application on volatile NH3‐N losses from cropland. In addition, a greenhouse study was conducted to determine the effect of wind on the rate of NH3‐N volatilization from soil and the accuracy of NH3‐N loss measurements under field conditions. A partially closed system was utilized to directly collect volatilized NH3‐N from microplots.The NH3‐N collection system did not accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
33
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 0 publications
7
33
0
1
Order By: Relevance
“…3c). These values are in the mid-upper end of the range of reported reduction rates which vary from 22% (Hoff et al 1981) to nearly 100% (Frost 1994). Our results confirm that a large fraction of the NH 3 volatilization occurring when slurry is applied to crop residues can be avoided if the slurry and residues are immediately incorporated into the soil.…”
Section: Ammonia Volatilizationmentioning
confidence: 83%
See 1 more Smart Citation
“…3c). These values are in the mid-upper end of the range of reported reduction rates which vary from 22% (Hoff et al 1981) to nearly 100% (Frost 1994). Our results confirm that a large fraction of the NH 3 volatilization occurring when slurry is applied to crop residues can be avoided if the slurry and residues are immediately incorporated into the soil.…”
Section: Ammonia Volatilizationmentioning
confidence: 83%
“…Rapid incorporation of slurry following application has been shown to reduce volatilization of ammonia . However, the efficiency of incorporation has been shown to vary with local soil, slurry and meteorological conditions, resulting in reductions varying from 22% (Hoff et al 1981) to 98% (Frost 1994) compared with slurry left on the soil surface. Our objective was to quantify the impacts of soil incorporation of pig slurry applied on canola crop residues on NH 3 volatilization and soil nitrogen dynamics.…”
mentioning
confidence: 99%
“…Environmental concerns surrounding the use of swine manure are largely based on the escape of excess N from the soil through leaching, denitrification and volatilization (Evans et al 1977;Hoff et al 1981). Through proper manure management and application techniques, manure can be applied to meet crop N requirements (Chang and Entz 1996).…”
mentioning
confidence: 99%
“…There was a 67% decrease in NH 3 concentration when liquid manure was applied by subsurface injection vs. surface or Aerway application, which did not differ. Hoff et al (1981) reported an 80% decrease in NH 3 losses by injecting liquid swine manure compared with surface application. Morken and Sakshaug (1998) reported a decrease of 62% in NH 3 losses when manure slurry was injected directly into the ground vs. surface applied.…”
Section: Resultsmentioning
confidence: 99%